Less for More: Enhancing Sustainability through Lean Operations - Nawanir, Gusman; Lim, Kong Teong; Maarof, Mohd Ghazali; Adeleke, A. Q.; Rahamadulla, Syed Radzi (Suara UMP, 2020)
Recently, the increase in resource consumption, climate change, biodiversity, water scarcity, and demographic changes and instability triggered the society to consider sustainability issues by taking the triple bottom line dimensions (or otherwise noted as 3BL) (Elkington & Rowlands, 1999) into organizational activities, namely economy, social and environment. Malaysia is committed to pursuing sustainable development based on three pillars, namely high income, inclusivity, and sustainability, which mirrors the 3BL dimensions of sustainable development goals.